Amplified delivery of indium-111 to EGFR-positive human breast cancer cells. - Wang, J; Chen, P; Su, Z; Vallis, K; Sandhu, J; Cameron, R; Hendler, A; Reilly, R (2001)
A method is described to amplify the delivery of 111In to human breast cancer cells utilizing a novel human serum albumin-human EGF (HSA-hEGF) bioconjugate substituted preferentially in the HSA domain with multiple DTPA metal chelators for 111In. 111In-DTPA-HSA-hEGF exhibited a lower receptor-binding affinity than 111In-DTPA-hEGF but was rapidly and specifically bound, internalized and translocated to the nucleus in EGFR-positive MDA-MB-468 breast cancer cells. 111In-DTPA-HSA-hEGF was cytotoxic in vitro mainly through the emission of short-range Auger electrons and partially through the effects of the hEGF moiety to MDA-MB-468 cells overexpressing EGFR (1-2 x 10(6) receptors/cell) but not towards MCF-7 breast cancer cells with a 100-fold lower level of EGFR on their surface. The cytotoxicity in vitro against MDA-MB-468 cells of 111In-DTPA-HSA-hEGF substituted with nine DTPA chelators was enhanced 4-fold compared to 111In-DTPA-hEGF monosubstituted with DTPA. Studies are planned to further evaluate 111In-DTPA-HSA-hEGF in vivo as a new imaging and targeted radiotherapeutic agent for breast cancer.